Reserve of ice in glaciers on the Nordenskiöld Land, Spitsbergen, and their changes over the last decades - I. Lavrentiev I.; A. Glazovsky F.; Yu. Macheret Ya.; V. Matskovsky V.; A. Muravyev Ya.; И. Лаврентьев И.; А. Глазовский Ф.; Ю. Мачерет Я.; В. Мацковский В.; А. Муравьев Я. (Ice and Snow, 2019)
Data on thickness and area of 16 glaciers on the Nordenskiöld Land (Svalbard) were obtained in 1999 and 2010–2013. These data were used to determine volume of the glaciers and to establish statistical local relationship between the volume V and the area A (V–A scaling) in the form of the power function V = cAγ, and then to calculate the total ice volume of all 202 glaciers in this area and its changes during the period since 1936 to 2002–2008. The total area of 16 glaciers was 129.9±0.35 km2, 14 of which had areas from 0.2 to 8.1 km2. The two largest ones, the Fridtjof and the West Grenfjord, had the areas 17.5 and 47.3 km2, respectively, and thus occupied about 50% (64.8 km2) of the total area of 16 glaciers. These two glaciers account for 67% of the total measured volume (10,034 km3) of the 16 glaciers. A nonlinear least-squares method was used to estimate ice reserves in all 202 glaciers from data on the volume and area of 16 glaciers. The relation between volume V and area A of the glaciers (V–A scaling) was obtained as the ratio V = 0.03637A1,283 with 95%‑th confidence intervals of the coefficients с and γ, (0.02303–0,4971) and (1.184–1.381), respectively. This made possible to calculate total volume of 202 glaciers as of 2002-2008 state using data from RGI v.6.0, and that prove to be equal to 32.89 (16.75–56.63) km3. To verify this estimation, we applied the bootstrapping method for chosen 43 glaciers and calculated the volume by means of sequential use of data for large and smaller glaciers. According to this estimate, the total volume of 202 glaciers amounted to 30.34 km3 with a 95% confidence interval of 15.42–44.27 km3, that turned out to be slightly smaller than the volume calculated by nonlinear least squares method basing on measurements on 16 glaciers. Despite the large error (on the average, from −49% to +84%) in estimating the total volume of 202 glaciers in the Nordenskiöld Land, the data obtained were used for assessment of relative changes in the total volume of glaciers in this area over ...